Mixed stock analysis of juvenile green turtles aggregating at two foraging grounds in Fiji reveals major contribution from the American Samoa Management Unit - Piovano, Susanna; Batibasaga, Aisake; Ciriyawa, Ana; LaCasella, Erin L.; Dutton, Peter H. (Scientific reports, 2019)
In this study we assessed the breeding population, or Management Unit (MU), origin of green turtles ( Chelonia mydas ) present at Yadua Island and Makogai Island foraging grounds in Fiji, central South Pacific. Based on analysis of mitochondrial (mt) DNA sequences from 150 immature green turtles caught during surveys carried out in 2015–2016, we identified a total of 18 haplotypes, the most common being CmP22.1 (44%) which is a primary haplotype characterizing the American Samoa breeding population. Results of a Bayesian mixed-stock analysis reveals that the two foraging grounds are used by green turtles from the American Samoa MU (72%, Credible Interval (CI): 56–87%), New Caledonia MU (17%, CI: 6–26%) and French Polynesia MU (7%, CI: 0–23%). The prominence of the contribution we found from the American Samoa MU compared to that of French Polynesia, both which have historic telemetry and tagging data showing connectivity with Fijian foraging areas, may reflect the current relative abundance of these two nesting populations and draws attention to a need to update population surveys and identify any significant nesting in Fiji that may have been overlooked.